The challenge of restoring tropical freshwater ecosystems - Reinaldo Luiz Bozelli (Acta Limnologica Brasiliensia, 2019)
Abstract We are living a growing worldwide process of degrading the bases of sustaining life. In Brazil, this threat is intensified by the growing fragility of environmental protection structures. Ecological restoration is an alternative to face the degradation of aquatic environments. It has been employed on a larger scale in the developed regions of the planet, but with little convincing results. In Brazil, the experiences are few and specific, limited mainly by complexity and costs. It is necessary to think in a more agile way and act within the possibilities. The restoration with its classic strategies should give way to an “urgent restoration”. This approach considers that we have the basic ecological information and professionals able to act in the resumption of control of the ecological processes that have been altered. Restoration in the condition of urgency implies beginning to think of protection, as a first step, turning attention to the management of the watershed. The way to regain control of the process where it was lost is the integrated management that involves the rational use and protection of the ecosystem. Brazil’s commitment to the Paris climate agreement to restore 12 million hectares of forests and the restoration liabilities on private properties because of the recent Native Vegetation Protection Law are excellent opportunities to act in the integrated management of the river basin and to promote the protection of freshwaters by the restoration of native forests. The restoration of tropical freshwaters and especially the Brazilian ones is something urgent. However, possible solutions must be thought of and can only be constructed when one get involved most people related to the issue. The idea to be nurtured is that restoration involves thinking about the watershed because the threats are beyond the aquatic environment itself, the restoration then also needs to go beyond the aquatic environment itself.